Sexual violence against minor girls: Strengthening the protective environment in the city of Porto-Novo - BIGA BOUKARY, Alassane; DAKPO, PASCAL CODJO; WABI, SAKARIYAOU ALABI (My University, 2018)
This study aims to contribute to the improvement of female minor’s protection system against sexual violence through strengthening the environment in the city of Porto-Novo. The survey is qualitative and quantitative type concerned 209 subjects including 189 young students and apprentices, and 20 child protection actors is to say 3 responsible for social promotion center, home to 1 Director, 1 Technical Assistant in Human Rights (TAHR), 11 players in the CGP, 1 child protection network president, 1 Social worker, and two legal assistants. The results reveal that the levels of protection system, protection strategies are much more developed in terms of prevention and in terms of management. Also, they have specific measures been taken to strengthen the protective environment and to reduce sexual violence. Furthermore, the study showed that some factors hindering the actions of prevention and support for victims, as presented by the multisectoral model. Examples are the lack of financial resources in structures, personnel insufficient, the persistence of subjective norms, the settlement and the resignation of some parents. This situation should raise questions and motivate the child protection structures to think better protection strategies.
Keywords: Sexual violence; underage girls; protection strategies; actors